Neural correlates of cocaine-induced conditioned place preference in the posterior cerebellar cortex - Rodríguez-Borillo, Olga; Roselló-Jiménez, Lorena; Guarque-Chabrera, Julian; Palau-Batet, María; Gil-Miravet, Isis; Pastor, Raúl; Miquel, Marta; Font, Laura (Frontiers in Behavioral Neuroscience, 2023)
Addictive drugs are potent neuropharmacological agents capable of inducing long-lasting changes in learning and memory neurocircuitry. With repeated use, contexts and cues associated with consumption can acquire motivational and reinforcing properties of abused drugs, triggering drug craving and relapse. Neuroplasticity underlying drug-induced memories takes place in prefrontal-limbic-striatal networks. Recent evidence suggests that the cerebellum is also involved in the circuitry responsible for drug-induced conditioning. In rodents, preference for cocaine-associated olfactory cues has been shown to correlate with increased activity at the apical part of the granular cell layer in the posterior vermis (lobules VIII and IX). It is important to determine if the cerebellum’s role in drug conditioning is a general phenomenon or is limited to a particular sensory modality. The present study evaluated the role of the posterior cerebellum (lobules VIII and IX), together with the medial prefrontal cortex (mPFC), ventral tegmental area (VTA), and nucleus accumbens (NAc) using a cocaine-induced conditioned place preference procedure with tactile cues. Cocaine CPP was tested using ascending (3, 6, 12, 24 mg/kg) doses of cocaine in mice. Compared to control groups (Unpaired and Saline animals), Paired mice were able to show a preference for the cues associated with cocaine. Increased activation (cFos expression) of the posterior cerebellum was found in cocaine CPP groups and showed a positive correlation with CPP levels. Such increases in cFos activity in the posterior cerebellum significantly correlated with cFos expression in the mPFC. Our data suggest that the dorsal region of the cerebellum could be an important part of the network that mediates cocaine-conditioned behavior.